2020
DOI: 10.1001/jamanetworkopen.2020.26698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electric Scooter Head and Neck Injuries in Paris, 2017-2019

Abstract: This case series study evaluates head and neck injuries caused by electric scooters in Paris, 2017-2019, focusing on user behavior and injury types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 7 publications
7
42
0
4
Order By: Relevance
“…Therefore, in the absence of other sources of information at a national level, we performed this analysis using news reports. Of note, despite this methodological issue, our findings are in line with other reports from other countries [ 3 , 4 , 6 , 7 , 9 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, in the absence of other sources of information at a national level, we performed this analysis using news reports. Of note, despite this methodological issue, our findings are in line with other reports from other countries [ 3 , 4 , 6 , 7 , 9 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the use of a helmet being associated with a lower risk of head injury, in our report, we observed that it was rarely used (2.1% of all cases) [ 17 ]. This finding is in line with a report from Paris and two from the United States reporting a rate of helmet use of 12%, 4.8%, and 2%, respectively [ 7 , 9 , 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most common injuries are head and facial trauma and extremity injuries. 1 , 2 , 3 , 4 , 5 Patients with these injuries are predominantly younger men, and substance use is also relatively common among the injured. 3 , 5 The characteristics of the injured and the prevalence of the sustained injuries have been reported by numerous authors.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 Patients with these injuries are predominantly younger men, and substance use is also relatively common among the injured. 3 , 5 The characteristics of the injured and the prevalence of the sustained injuries have been reported by numerous authors. We aimed to evaluate the incidence of e-scooter–related injuries.…”
Section: Introductionmentioning
confidence: 99%